Ethical challenges for employees in a time of pandemics and advances in artificial intelligence; or “is our psychology relevant any more”? - Kwiatkowski, Richard; Angus, Andrew; Aktas, Emel (European Association of Work and Organizational Psychology (EAWOP), 2023)
Our work is at an unusual intersection of professional psychology and professional business ethics. We partnered in an international survey examining ethical and unethical behaviour in industry. We make longitudinal comparisons of ethical behaviour with a focus on the ethical implications of Covid19 and the growing role of Artificial Intelligence in the work environment and in social lives.
Oral presentation OP782
Keywords: Ethics; Employee perceptions; Statistical Analysis